Sistem Informasi Perpustakaan Berbasis Client Server di SMK Bintara Rancaekek - Hamzah, Erika Revina; Nugraha, Muhamad Fahmi (Ma'soem University, 2024)
SMK Bintara Rancaekek still has an educational support system that has not been computerized, one of which is library management. The process of managing library data is handled by one officer, starting from searching for book data, recording loan transactions, return transactions, calculating fines, and generating reports, all of which are still done manually or have not been computerized. As a result, several issues arise, including difficulties in managing borrowing and returning data, time-consuming recapping, and the risk of recording errors and data loss. The purpose of this research is to assist officers in managing book data, visits, borrowing and returning transactions, as well as minimizing data loss and recording errors, simplifying the calculation of fines, and generating reports quickly. The method used in this research is the Rational Unified Process (RUP). The design uses analysis tools such as flowmaps, Data Flow Diagrams (DFD), Entity Relationship Diagrams (ERD), Data Dictionaries, and Structure Charts. The design and development of this library information system are expected to address the aforementioned problems and provide ease of operational work, especially in managing the borrowing and returning of library books.